PERBEDAAN PENGELUARAN ASI PADA IBU POSTPARTUM SEBELUM DAN SESUDAH DILAKUKAN PIJAT OKSITOSIN: PERBEDAAN PENGELUARAN ASI PADA IBU POSTPARTUM SEBELUM DAN SESUDAH DILAKUKAN PIJAT OKSITOSIN - Mulyani, Irma (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2021)
Background : Breast milk is the best food that meets all baby's growth and development needs until the age of 6 months. There are times when a mother experiences problems in breastfeeding which is because her milk production is little or not smooth. Oxytocin massage is one solution to overcome the not smooth production of breast milk. Research Purpose : To determine the difference in breast milk expenditure postpartum mothers 6 hours before and after oxytocin massage in Puskesmas Batujajar District West Bandung In 2019. Research Method : This research uses the method Quasi-experiment by design one group pre and post test design. The sampling technique uses accidental sampling, the sample in this study was 6 hours postpartum mothers amounted to 30 people. Data collection uses observation sheets. Data analysis was univariate and bivariate to see the frequency distribution and differences in breast milk expenditure before and after oxytocin massage. Results : Average breast milk expenditure before oxytocin massage was 1.50 cc and after the oxytocin massage increased to 2.93 cc. Conclusion : there is a difference between the expenditure of breast milk in postpartum mothers 6 hours before and after oxytocin massage. Keywords : Oxytocin massage, expenditures breast milk